An analytical expression for the dynamic active thrust from c-φ soil backfill on retaining walls with wall friction and adhesion - Shukla S.K.; Bathurst R.J. (My University, 2025)
This paper presents the derivation of an analytical expression for the dynamic active thrust from c-φ (c = cohesion, φ = angle of shearing resistance) soil backfill on rigid retaining walls with wall friction and adhesion. The derivation uses the pseudo-static approach considering tension cracks in the backfill, a uniform surcharge on the backfill, and horizontal and vertical seismic loadings. The development of an explicit analytical expression for the critical inclination of the failure plane within the soil backfill is described. It is shown that the analytical expression gives the same results for simpler special cases previously reported in the literature.